Interdisciplinary pharmacometrics linking oseltamivir pharmacology, influenza epidemiology and health economics to inform antiviral use in pandemics. (20th February 2017) - Kamal, Mohamed A.; Smith, Patrick F.; Chaiyakunapruk, Nathorn; Wu, David B. C.; Pratoomsoot, Chayanin; Lee, Kenneth K. C.; Chong, Huey Yi; Nelson, Richard E.; Nieforth, Keith; Dall, Georgina; Toovey, Stephen; Kong, David C. M.; et al.
Abstract : Aims: A modular interdisciplinary platform was developed to investigate the economic impact of oseltamivir treatment by dosage regimen under simulated influenza pandemic scenarios. Methods: The pharmacology module consisted of a pharmacokinetic distribution of oseltamivir carboxylate daily area under the concentration–time curve at steady state (simulated for 75 mg and 150 mg twice daily regimens for 5 days) and a pharmacodynamic distribution of viral shedding duration obtained from phase II influenza inoculation data. The epidemiological module comprised a susceptible, exposed, infected, recovered (SEIR) model to which drug effect on the basic reproductive number (R0 ), a measure of transmissibility, was linked by reduction of viral shedding duration. The number of infected patients per population of 100 000 susceptible individuals was simulated for a series of pandemic scenarios, varying oseltamivir dose, R0 (1.9 vs . 2.7), and drug uptake (25%, 50%, and 80%). The number of infected patients for each scenario was entered into the health economics module, a decision analytic model populated with branch probabilities, disease utility, costs of hospitalized patients developing complications, and case‐fatality rates. Change in quality‐adjusted life years was determined relative to base case. Results: Oseltamivir 75 mg relative to no treatment reduced the median number of infected patients, increased change in quality‐adjusted life years by deaths averted, and was cost‐saving under all scenarios; 150 mg relative to 75 mg was not cost effective in low transmissibility scenarios but was cost saving in high transmissibility scenarios. Conclusion: This methodological study demonstrates proof of concept that the disciplines of pharmacology, disease epidemiology and health economics can be linked in a single quantitative framework.